(untitled) (International Journal of Physiology, 2019)
Background Assessments, if suitably conducted, can serve several goals and provide many advantages to all stakeholders-the medical students, the teaching faculty, the universities and the society as a whole. Assessment in medical education is mostly of two forms either formative or summative. Although it is generally assumed that the performance of a student in formative assessment will act as a predictor for performance in the summative examination not many studies are available support it. Objectives To explore whether performance in the continuous internal assessment, correlates with the final summative assessment in first year medical students in the subject of Physiology for the last three years. Materials and Method This study was conducted over a period of six months at SKIMS medical college, Srinagar. It was a observational record-based study on 280 students who took a thorough internal assessment and final examination in the subject of physiology in the batches 2014–15, 2015–16 and 2016–17. Results The internal assessment marks showed a positive correlation with marks obtained in final assessment or final university exams in all three batches, which is statistically highly significant (p<0.01). It was also observed that the percentage of final university marks was higher as compared to internal assessment marks in all batches. Conclusion The present study revealed a positive correlation between internal assessment and final university marks supporting the general assumption that the performance of a student in formative assessment will act as a predictor for performance in the final summative examination.